Uma investigação sobre a formação docente e a integração das tecnologias da informação e comunicação nos cursos de licenciatura em física dos Institutos Federais do estado do Rio Grande do Sul - Guedes, Giane Tais Cruz (2020)
Nowadays, Information and Communication Technologies (ICT) are present in the daily lives of people in many sectors, including the equipment and entertainment industries. Thinking about teacher training, the literature indicates several references that aim at better training so that educators can select, elaborate and evaluate teaching strategies that are consistent with the demands of contemporary society, that start from their training objectives and that enhance the use of technologies in the teaching-learning process. These reasons lead us to analyze, through the Pedagogical Course Projects (PPC), the training of Physical Educators at the Federal Institutes of the State of Rio Grande do Sul, with the intention of understanding the process of training these people with regard to development of pedagogical practices using new technologies in a critical and creative way. To achieve the purposes of this research we used an investigation through the documental analysis of the pedagogical projects of the Physics degree courses at the Federal Farroupilha Institute and the Federal Sul Rio Grandense Institute. From this analysis, a pause for thought was made on the formation of these future educators and the use of ICT throughout the formative process. The investigation points out the importance of public policies and refers to the models of adoption / integration of ICTs that agree, among themselves, that integration does not occur instantly, but procedurally. This understanding demonstrates how important it is to expand the contact and experience of teachers with these technologies since the initial training process. Disciplines such as teaching methodology, instrumentation and internships present excellent opportunities to contemplate the use of these resources. After analyzing the PPC of the courses, two online questionnaires were designed for teachers and graduates of the courses in question. For data analysis we used the Discursive Textual Analysis (DTA) and with it we identified the main challenges for training based on the speeches of the teachers, which led us to three categories for the analysis of the teachers’ questionnaire: Presence of Technologies in the practice of teaching; Concern with the integration of ICT in the disciplines and Importance of Technologies in Teacher Training. Likewise, the analysis of the graduates' questionnaires led us to three categories: Contributions of ICT in the formative process of the Physics teacher; Training for the use of Technologies; and analysis of ICT in the classroom. In short, this research contributed to the need to think about a less fragmented formative structure, in which ICT - and not only them - are discussed in different contexts and environments, in order to go beyond the PPC of the Physics Degree course institutions that participated in this research.